The Concept of the Poet in Latif Halmet’s Poetic Text - Pshtiwan Asaad Karem; Salim Rashid Salih (Zanco Journal of Humanity Sciences)
The concept of the poet; Thanks to his invention—poetry—difference, function and source of invention; It has been viewed from many perspectives, from ancient times to the present; It has been identified as crazy, innovative, talented and experienced, depending on its different views and the role and position of his innovation.